The incidence of inherited metabolic disorders in the West Midlands, UK. Issue 11 (11th May 2006) - Sanderson, S; Green, A; Preece, M A; Burton, H
Abstract : Background: Inherited metabolic disorders (IMDs) are a heterogeneous group of genetic conditions mostly occurring in childhood. They are individually rare but collectively numerous, causing substantial morbidity and mortality. Aims: To obtain up-to-date estimates of the birth prevalence of IMDs in an ethnically diverse British population and to compare these estimates with those of other published population-based studies. Methods: Retrospective data from the West Midlands Regional Diagnostic Laboratory for Inherited Metabolic Disorders (Birmingham, UK) for the 5 years (1999–2003) were examined. The West Midlands population of 5.2 million is approximately 10% of the UK population. Approximately 11% of the population of the region is from black and ethnic minority groups compared with approximately 8% for the the UK. Results: The overall birth prevalence was 1 in 784 live births (95% confidence interval (CI) 619 to 970), based on a total of 396 new cases. The most frequent diagnoses were mitochondrial disorders (1 in 4929; 95% CI 2776 to 8953), lysosomal storage disorders (1 in 5175; 95% CI 2874 to 9551), amino acid disorders excluding phenylketonuria (1 in 5354; 95% CI 2943 to 9990) and organic acid disorders (1 in 7962; 95% CI 3837 to 17 301). Most of the diagnoses (72%) were made by the age of 15 years and one-third by the age of 1 year. Conclusions: These results are similar to those of the comparison studies, although the overall birth prevalence is higher in this study. This is probably due to the effects of ethnicity and consanguinity and increasing ascertainment. This study provides useful epidemiological information for those planning and providing services for patients with IMDs, including newborn screening, in the UK and similar populations.